Implementasi Undang-undang Nomor 44 Tahun 2008 Tentang Pornografi (Studi Kasus Aplikasi Bigo Live Sebagai Sarana Komunikasi Sosial) - hadianto ego gantiano; Tardi Edung (Belom Bahadat, 2019)
This scientific article analyzes the application of the Pornography Law to the actions of Bigo Live / Host Bigo Live application users, using content analysis or content related to communication logic, that every communication always contains a message in the communication signal. In this study using a participant approach where the author participates in the development of the use of the Bigo Live application, when the research is carried out for three months. The results of this study are the large number of Bigo Live application service users, whether spectators or hosts, who violate the Law on Pornography, use of the application is misused to meet sexual needs, and hosts who are usually women show a lot of content that should be regulated in the law pornography.